Drying studies in Indian bay leaf (Cinnamomum tamala (Buch.-Ham.) T. Nees & Eberm) under warm and humid conditions of the Bay Islands: Drying studies in Indian bay leaf - Ghosh, Sohini; Waman, Ajit Arun; Bohra, Pooja; Karthika Devi, R (Journal of Spices and Aromatic Crops, 2025)
Indian bay leaf or tejpat (Cinnamomum tamala (Buch.-Ham.) T. Nees & Eberm) is an important spice that has been used for flavouring of cuisines and as an ingredient in pharmaceutical and allied industries. At present, the leaves are largely harvested from the trees grown in the backyards or from the wild and dried under the sun or shade in most of the growing areas. However, as the cultivation of the crop is also extending in non-native regions of this crop including the Bay Islands, identification of region-specific method of drying was envisaged. In the present study, five drying methods viz. vacuum drying, sun drying, oven drying (45 °C and 55 °C) and air drying were compared to know their effect on quality parameters of tejpat under island conditions. Moisture content in the fresh samples was 49.89%, which was reduced to 4.54% (sun drying) to 6.78% (air drying). The dry recovery was found to be the highest in air drying. Oleoresin content was highest in the sun drying method, while essential oil content did not vary. Chlorophyll a, chlorophyll b and total chlorophyll content were found to be the highest in air dried samples, which remained on par with vacuum drying. Total carotenoids content was the highest in case of vacuum drying. RHS colour chart codes exhibited variations among the dried produce. Considering the better dry recovery, better retention of chlorophyll content and ease of operation, air drying could be recommended for farm level processing of tejpat under warm and humid areas. In the times of high rainfall and humidity, mechanical drying could be adopted to facilitate better drying.